2016
DOI: 10.1088/1361-6498/37/1/59
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of ionizing radiation exposure among junior doctors and senior medical students in radiological investigations

Abstract: The awareness and knowledge of ionizing radiation exposure in radiological investigations among junior doctors and medical students were studied. The participants were year four to year six senior medical students enrolled at University of Dammam and interns in King Fahad University Hospital. The survey consisted of 22 questions designed online using the software 'QuestionPro' licensed to the University of Dammam. 100 hard copies were also distributed manually and collected. A total of 221 (88.5%) questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…So far, the results of such studies, including the current study, have been concerning. Numerous studies have been conducted in recent years among medical students and physicians for that our purpose [17,18,22,23,[26][27][28][29][30][31][32][33]. Previous studies have shown concerning results indicating that both healthcare professionals and trainees are not sufficiently familiar with radiological dosage and relevant hazards [10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…So far, the results of such studies, including the current study, have been concerning. Numerous studies have been conducted in recent years among medical students and physicians for that our purpose [17,18,22,23,[26][27][28][29][30][31][32][33]. Previous studies have shown concerning results indicating that both healthcare professionals and trainees are not sufficiently familiar with radiological dosage and relevant hazards [10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Radiation workers are subject to ionizing radiation exposure during the procedures of common radiological investigations. Therefore, the awareness and knowledge of radiation dose exposure are important [3]. In Saudi Arabia, medical imaging applications provided by computed tomography have significant benefits, leading to an increase in the use of CT scanners and healthcare technology.…”
Section: Introductionmentioning
confidence: 99%
“…Almohaimede et al conducted a similar study and reported that radiation risks were well understood; however, radiation safety precautions should be stressed more among general practitioners in governmental and private sectors [ 8 ]. Ionizing radiation doses were not well understood or widely known in imaging radiology among young clinicians and senior medical students within the study fields [ 9 ]. In the detection of several dental problems, CT, especially its derivatives 3D CT and ortho cubic super-high-resolution CT, and the clinically applicable artificial intelligence system recently become the method of choice [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%